Cleft lip and palate – a comparative psychosocial study - Nicholls, Wendy (Curtin University, 2017)
There are considerable psychosocial impacts associated with the condition of cleft lip and palate (CL/P). This thesis investigated patient perceived impacts of CL/P on psychosocial adjustment and sociological life outcomes across three age-groups, and the perceptions of healthcare professionals with regard to confidence in treating those with CL/P. A mixed methods approach found that CL/P had been a lifelong challenge which resulted in positive educational and employment outcomes but poorer relationship and psychosocial outcomes.